D-OPTIMAL MIXTURE DESIGN: OPTIMIZATION, FORMULATION, AND EVALUATION OF BIOSYNTHESIS NANOGOLD GELS - PERTIWI, RATIH DYAH; SETYOWATI, ERNA PRAWITA; MARTIEN, RONNY; SUWALDI (International Journal of Applied Pharmaceutics, 2023)
Objective: The aim of this research is the Optimization, formulation, and evaluation of biosynthesis nanogold gels by using experimental design. Investigations were provided to optimize the biosynthesis of nanogold gels on a compound of two gelling agents and develop the biosynthesis of nanogold gels. Methods: The optimization of the formula of gels utilizing the D Optimum Mixture Design method to discover the optimum result with the ratio of carbopol (X1) and hydroxypropyl methylcellulose/HPMC (X2) as a gelling agent and responses in the form were particle size (Y1), zeta potential (Y2) and spreading capacity (Y3). The 8-run formula assessed the impact of carbopol (X1) and HPMC (X2). Results: The ANOVA results for particle size showed that the model is highly statistically significant (P<0.05). Both Carbopol and HPMC coefficients enhanced the particle size (+118.91 and+594.73). The interaction of Carbopol with HPMC has increased the particle size (+441.73). The HPMC has the most dominant effect in increasing the particle size, and exchanging the two gelling agents will increase the particle size. Both Carbopol and HPMC coefficients are negative (-7.94 and-10.96), which means that these components contribute to a decrease in the zeta potential. The interaction of Carbopol with HPMC does not affect both increasing or decreasing the zeta potential HPMC has the most dominant effect in reducing the zeta potential, and the exchange of the two gelling agents will not increase and decrease the zeta potential. Carbopol and HPMC coefficients are positive (+6.41 and+4.58), meaning these components enhance the spreading capacity. The interaction of Carbopol with HPMC has decreased (-1.58). The prediction value was obtained from a solution that has the highest desirability. The chosen desirability of certain balances was 0.572. Conclusion: This study has shown that a well-balanced mixture of matrix ingredients could improve nanogold biosynthesis gel. Optimization was possible by applying D optimal mixture design, which confirmed efficiency in designing the nanoparticles gels of gold dosage forms.